Verification of Newly FDA-Approved Kappa and Lambda Free Light Chain Assays on a Previously Untested Platform. (19th November 2019) - Muluhngwi, Penn; Sharp, Cierra N; Pozzi, Nicole; Elin, Ronald J; Jortani, Saeed A
Abstract: Background: κ and λ free light chains (FLCs) are monitored to aid in the diagnosis of plasma cell disorders. Our goal was to validate the Diazyme Human κ and λ assays on Beckman Coulter UniCel DxC 800 Synchron and compare to Freelite κ and λ assays on Roche Cobas Integra. Methods: Linearity verification, within- and between-run precision, method comparison, and reference range (RR) verification were conducted using CLSI guidelines. Statistical analysis was performed using EP Evaluator ® . Mean, SD, CV, and bias were determined. Results: Diazyme κ FLC assay was linear within 0.00–191.00 mg/L. Diazyme λ FLC assay was linear within 0.00–205.30 mg/L. Diazyme κ FLC QC1 had a mean of 16.70 mg/L, CV of 7.0%. QC2 had a mean of 33.37 mg/L, CV of 2.6%. Diazyme λ FLC QC1 had a mean of 21.73 mg/L, CV of 2.3%. QC2 had a mean of 42.05 mg/L, CV of 1.5%. Bias of DxC-Diazyme FLCs compared to Integra-Freelite FLCs was −2.55 mg/L (κ FLC), and 4.54 mg/L (λ FLC). Qualitative comparison of κ FLC assays indicated 100% agreement for both normal and abnormal values. For λ FLC assay, agreement was 95% for normal values and 75% for abnormal values. For κ/λ ratio there was 50% agreement for normal values, and 100% for abnormal values. For RR verification, 1 sample was outside the Diazyme κ RR. For λ, all samples were within the manufacturer's RR. Conclusions: Diazyme assays for FLCs have excellent precision and accuracy and are comparable to Freelite assays.